The toxic effects of p-Cresyl Sulfate on bone metabolism - Ahmad Faizal, Jelani; Gabrielle Ruth Anisah, Fromming; Dayang Erna Zulaikha, Awang Hamsin; Mohammad Zulkarnaen, Ahmad Narihan (Springer Nature Switzerland, 2022)
Background p-Cresyl Sulfate (pCS) is a uremic toxin that has been implicated in kidney disease, cardiovascular risks, endothelial dysfunction and neuropathies. In chronic kidney disease (CKD), pCS progressively accumulates in the body as the dysfunctional kidneys have a reduced ability to excrete toxins normally. pCS accumulated as a consequence of CKD cannot be removed from th body through dialysis, hence leading to further accumulation. This ultimately leads to bone loss which correlates with the worsening of CKD. As such, pCS could play a part in the development of bone loss with CKD. The objective of this review is to further understand the comprehensive effects pCS has on the bone.